Generalization of some extremal properties of splines - Babenko, V. F.; Ligun, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We generalize well-known inequalities for the norms of the derivatives of periodic splines with minimal defect, perfect splines, and monosplines.